Islam Nusantara: Relasi Islam dan Budaya Lokal - Luthfi, Khabibi Muhammad (SHAHIH: Journal of Islamicate Multidisciplinary, 2016)
The objective of this article is to explore the concept ofÂ Islam NusantaraÂ (IN)Â observed from the structural theory of Islam and local culture relation, along with the reason why INÂ is developed into the concept of the Islamic proselytizingÂ Rahmatan lilalaminÂ by the intellectualÂ Nahdhatul UlamaÂ (NU). It comes from the NU Intellectuals claim that IN is the mediator in the controversy of Islam and local culture relation, moreover in the global scale it is going to be proselytized in the International, whereas the IN is still regarded as an issue and has not fulfilled the knowledge standard yet. Through philosophical approach, socio-anthropolinguistics based on the data inÂ www.nu.or.idÂ and topic analysis as its data analysis, it is found that the intellectualÂ of NUÂ used eight approaches to concept the IN.Â TheÂ INÂ set that Islam influences Indonesian culture and the INs success and ability to dialogue with Indonesian culture trigger the intellectual NU to promote it to the International.